Los extranjeros en México y los mexicanos en el extranjero, 1821-1970. - González Navarro, Moisés (Colegio de México, Centro de Estudios Históricos, 1994)
This is a macro history of Mexico, from the perspective of foreigners who immigrated to the country and Mexicans who emigrated from it, based largely on primary printed sources, unpublished sources, and monographs. In the second volume, with freedom of religion already established, a liberal atmosphere opens up that reduces the problem of choosing between Saxon and Latin immigrants. Among the first, the Mormon colonization stands out; among the latter, the Italian. The traditional mistrust of the Americans transforms xenophilia into xenophobia. In addition, the increasing departure of braceros to the United States confirms that Mexico is a country of emigration and not of immigration.